Research on the practice of enhancing the regularization management of government full-time fire brigade - Wu, Wenya; Liu, Yixing; Chen , Minghou (Transactions on Economics, Business and Management Research, 2024)
With the development of the social economy, the demand for fire safety among the people is increasing, and the problem of insufficient fire protection forces is becoming increasingly prominent. Therefore, developing a dedicated government fire brigade has become an effective way to solve this problem. This article aims to explore practical methods for improving the standardized management and professional construction of the government’s full-time fire brigade. This article first analyzes the current situation of the government’s full-time fire brigade, including problems in personnel establishment, salary and benefits, management system, and other aspects. Furthermore, it was discussed how to enhance the standardized management and professional construction of the government’s full-time fire brigade, including improving organizational structure, clarifying responsibilities and functions, standardizing duty models, and increasing the level of professionalism. In addition, several considerations were also mentioned to strengthen the construction of the government’s full-time fire brigade, including strengthening organizational leadership, improving guarantee mechanisms, and promoting standardized construction.